2006
DOI: 10.1007/s00421-006-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Central adaptations during repetitive contractions assessed by the readiness potential

Abstract: Physiological fatigue, a loss of maximal force producing capacity, may originate both from changes at the peripheral and at the central level. The readiness potential (RP) provides a measure to study adaptations to physiological fatigue at the motor cortex. We have studied the RP in the course of repetitive contractions at a high force level. Fourteen female healthy subjects made repetitive force grip contractions at 70% of their maximal voluntary contraction (MVC) for 30 min. Contractions were self-paced and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 26 publications
4
49
2
1
Order By: Relevance
“…The study confirmed that the pre-motor brain activity increases with muscle fatigue (e.g. Liu et al 2005;Schillings et al, 2006;Falvo et al, 2011) and with the subjectively perceived exertion (Slobounov et al, 2004;de Morree et al, 2012). In particular, they showed that muscle fatigue modulates the activity in the SMA and PMA, as indexed by the larger amplitude of the BP and NS' in the fatigued participants.…”
Section: Section 5 Fatiguing Actionssupporting
confidence: 79%
See 2 more Smart Citations
“…The study confirmed that the pre-motor brain activity increases with muscle fatigue (e.g. Liu et al 2005;Schillings et al, 2006;Falvo et al, 2011) and with the subjectively perceived exertion (Slobounov et al, 2004;de Morree et al, 2012). In particular, they showed that muscle fatigue modulates the activity in the SMA and PMA, as indexed by the larger amplitude of the BP and NS' in the fatigued participants.…”
Section: Section 5 Fatiguing Actionssupporting
confidence: 79%
“…Liu et al, 2005;Schillings et al, 2006). Nevertheless, Liu et al (2005) failed to observe any change during the motor preparation processing, and Schillings et al (2006) did not distinguish between the NS' and the MP components. On the other hand, other authors observed an attenuation of the BP during fatiguing tasks (Kristeva, 1977;Popivanov, Mineva, and Dushanova, 1995), which was interpreted as a decreased intentional involvement and result of habituation processes.…”
Section: Section 5 Fatiguing Actionscontrasting
confidence: 61%
See 1 more Smart Citation
“…Tijdens herhaalde willekeurige contracties die tot vermoeidheid leiden kunnen veranderingen in de premotorische potentiaal en daarmee veranderingen in de centrale aansturing gemeten worden. 10 Vermoeidheid is een klacht die bij neurologische patiënten veelvuldig voorkomt.…”
Section: Centrale Vermoeidheidunclassified
“…Most investigations have found progressive increases and widespread changes in cortical activity during repetitive movements [4,15,20,21,22,23,24,25,26]. However, these investigations have varied in their use of incremental or non-incremental loading, the biomechanical aspects of movement, and whether or not fatigue was a specific outcome variable.…”
Section: Introductionmentioning
confidence: 99%